Sheet metal forming simulation using finite elastoplasticity with mixed isotropic/kinematic hardening - Chatti, Sami; Chtioui, Narjess (European Journal of Computational Mechanics, 2011)
A numerical formulation is presented for anisotropic elastoplasticity behavior in finite strain with non-linear isotropic/kinematic hardening model. Non-linear kinematic hardening is modeled by the Lemaitre-Chaboche law with the aim of considering cyclic deformation phenomena. User-defined material subroutines are developed based on Hill’s quadratic yield function for both ABAQUS-Explicit (VUMAT) and ABAQUS-Standard (UMAT). For validation purpose, the tension-compression and cyclic shear tests are simulated. Several sheet forming processes including contact, anisotropic plasticity, elastic modulus variation with plastic strain and springback effects are simulated. Numerical results are compared with experimental data.